PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN (SURVEI PADA BANK JAWA BARAT BANTEN KANTOR CABANG SUCI BANDUNG) - Shielpani, Amalia; Firmansyah, Yayan (Jurnal Manajemen Magister Darmajaya, 2018)
The purpose of this study was to examine the influence of organizational culture, competence, and performance both partially and simultaneously.The method used in this research is verification method. The object population of the study was 62 employees, sampling using census methods. The findings in this study are partially first; Organizational culture contributes positively to employee performance by 22%, secondly the influence of competence on employee performance is 41%, while simultaneously the influence of organizational culture and competence on performance is 63.1%.One of management's efforts in improving employee performance needs to pay attention to introducing organizational culture by way of new employee orientation and competence by providing training that supports work such as communication and negotiation training. Whereas for further research can expand the object of research or add variables and other indicators that affect employee performance.With the disclosure of these variables, it will enrich the references regarding Organizational Culture and Competence to the Bank Jabar Banten Employee Performance variable. It is hoped that later the resulting data can further reveal the variables under study so as to further strengthen and enrich the results of the research.Keywords: Organizational Culture, Competence, Employee Performance.